The effect of inlet temperature and pump flowrate of 5% carboxymethyl cellulose (CMC) in spray dryer: article - Misni, Muhammad Zaidi; Abd Hashib, Syafiza; Abd Rahman, Norazah (2017)
The used of CMC in industry are increasingly by year due to multipurpose usage such as in food industry, paint industry, pharmaceutical industry and paper making industry. CMC is cellulose derivative with carboxymethyl group attached to some of the hydroxyl group of glucopyranose monomers that make up cellulose backbone. CMC often used as sodium carboxymethyl cellulose because it’s easy for transportation compared to CMC in liquid form. Most of the CMC usage is in food industry as a binding agent to make the product become more durable or use as a thickener. CMC in food industry used E466 as its identification number (C. B. Hollabaugh, 1945). CMC is extracted from palm oil empty fruit bunch. CMC converted to solid powder by using spray dryer technology. Sample collected than analyze using pH meter, moisture content and solubility.